Association of Genetic Polymorphisms in FOXA1 with the Progression of Genetic Susceptibility to Gastric Cancer - Guo-wen Ding; Xu-yu Gu; Zhe Dai; Hui-wen Pan; Xiao-yan Wang; Heng Zhang; Yu Fan (Gastroenterology Research and Practice)
Objective. To investigate the relationship between polymorphism of FOXA1 gene rs12894364 and rs7144658 and susceptibility to gastric cancer. Methods. A case-control study was conducted to select 577 cases of primary gastric cancer and 678 cases of normal control. We extracted whole blood genomic DNA and amplified the target gene fragment by PCR. The genotyping and allele was tested through a snapshot method. Results. There was no significant difference in the frequency distribution of genotype between the case group and control group (P>0.05). Stratified analyses showed the SNPs were not correlated with the susceptibility of GC according to different age, gender, cigarette smoking, and alcohol drinking status. Conclusion. There is no significant correlation between the polymorphisms of FOXA1 gene rs12894364 and rs7144658 and the risk of gastric cancer.